2014
DOI: 10.1080/10255842.2014.887698
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of non-Newtonian blood flow dynamics in human thoracic aorta

Abstract: Three non-Newtonian blood viscosity models plus the Newtonian one are analysed for a patient-specific thoracic aorta anatomical model under steady-state flow conditions via wall shear stress (WSS) distribution, non-Newtonian importance factors, blood viscosity and shear rate. All blood viscosity models yield a consistent WSS distribution pattern. The WSS magnitude, however, is influenced by the model used. WSS is found to be the lowest in the vicinity of the three arch branches and along the distal walls of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(39 citation statements)
references
References 59 publications
4
35
0
Order By: Relevance
“…Despite the fact that the blood flow in the vascular system was pulsatile under physiological conditions, several numerical [73,74] and in vitro [75][76][77] studies have suggested that steady-state simulation can predict the non-temporal related flow characteristics at the corresponding point of the pulsatile flow profile. In addition, it has been reported that the WSS distribution patterns derived from the steady flow simulations are similar to the time-averaged WSS (TAWSS) from the unsteady analyses [67,78,79].…”
Section: Modeling Simplificationsmentioning
confidence: 68%
“…Despite the fact that the blood flow in the vascular system was pulsatile under physiological conditions, several numerical [73,74] and in vitro [75][76][77] studies have suggested that steady-state simulation can predict the non-temporal related flow characteristics at the corresponding point of the pulsatile flow profile. In addition, it has been reported that the WSS distribution patterns derived from the steady flow simulations are similar to the time-averaged WSS (TAWSS) from the unsteady analyses [67,78,79].…”
Section: Modeling Simplificationsmentioning
confidence: 68%
“…The results presented in Figure 15 show that the employed CFD simulations are appropriate enough to be used in the computations of HAHTs. References [35][36][37] measurements, at least in the three computed TSR, a fact that is attributed to the better performance of the SST model regarding the k-ε model in these kinds of rotating machines [27]. The results presented in Figure 15 show that the employed CFD simulations are appropriate enough to be used in the computations of HAHTs.…”
Section: Comparison Of Cfd Simulations With Other Sourcesmentioning
confidence: 99%
“…A literature study conducted for this research [3][4][5] shows that computational grids created for the analysis of blood flow in an artery are, typically, unstructured triangular and tetrahedral meshes prepared for inviscid computations The results of the numerical analysis of blood flow ⇤ e-mail: natalia.gr.lewandowska@doctorate.put.poznan.pl conducted on such meshes are flawed. Low quality and no inflation layer grids do not provide the necessary resolution to model the detachment of the boundary layer in the flow.…”
Section: Introductionmentioning
confidence: 99%